Mit Anarhhia Jeyan Re (Auto Biography) - Mandi, Aditya Kumar (Balika Mandi Bankura West Bengal, 2009)
It is an autobiographical book witten by Aditya Kumar Mandi
Keywords: Mit Anarhhia Jeyan Re (Auto Biography); Autobiography; Santali